Towards an open framework for adaptive, agent-supported e-learning. (6th September 2005) - Van Rosmalen, Peter; Brouns, Francis; Tattersall, Colin; Vogten, Hubert; Bruggen, Jan; Sloep, Peter; Koper, Rob
E-learners require activities and content based on their preferences and prior knowledge, not merely fully static, page-turning sequences. In this paper, we present a framework that integrates and supports two approaches towards adaptation to the learner needs – design and runtime adaptation. The framework is based on IMS Learning Design (IMS LD). IMS LD offers a semantic notation to describe an educational scenario in a formal way. At design time, a teacher or a design team can create or inspect a learning design model and use it in multiple courses. At runtime, a tutor or agent, an autonomous piece of software, can interpret a learning design and students' progress and subsequently take action while a course is in progress, e.g. make suggestions to learners. We will discuss the study that lead to the framework, and explain the role of IMS LD and the promising role of agents in adaptive e-learning.